2022
DOI: 10.3389/fpls.2022.906207
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Damage Based Phenotyping Technique and Its Validation Against Fall Armyworm, Spodoptera frugiperda (J. E. Smith), in Maize

Abstract: Globally, maize is an important cereal food crop with the highest production and productivity. Among the biotic constraints that limit the productivity of maize, the recent invasion of fall armyworm (FAW) in India is a concern. The first line of strategy available for FAW management is to evaluate and exploit resistant genotypes for inclusion in an IPM schedule. Screening for resistant maize genotypes against FAW is in its infancy in India, considering its recent occurrence in the country. The present work att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The lack of significant difference between leaf damage and grain yield in the other cases of this study agrees in part with the results by Britz, [33], who reported that plants with low to moderate damage scores did not suffer significant yield losses. Plant response to damage is influenced not only by the severity of symptoms, but also by factors such as drought conditions [34], soil nutrient status [35], the length of the larval feeding period, and the inherent level of plant resistance to larval feeding damage [36]. These factors, not documented in this study, solely or interactively could have influenced the results of this study.…”
Section: The Relationship Between Yield and Spodoptera Frugiperda Lea...mentioning
confidence: 77%
“…The lack of significant difference between leaf damage and grain yield in the other cases of this study agrees in part with the results by Britz, [33], who reported that plants with low to moderate damage scores did not suffer significant yield losses. Plant response to damage is influenced not only by the severity of symptoms, but also by factors such as drought conditions [34], soil nutrient status [35], the length of the larval feeding period, and the inherent level of plant resistance to larval feeding damage [36]. These factors, not documented in this study, solely or interactively could have influenced the results of this study.…”
Section: The Relationship Between Yield and Spodoptera Frugiperda Lea...mentioning
confidence: 77%
“…In addition, the resistance levels of several germplasms were flexible or unstable in different rounds of identification, as one germplasm would shift from one resistance level to another level, while the 12 varieties mentioned above were steadily kept at their fixed resistant levels in any round of identification. The phenomenon of the scarcity of resistant germplasm resource is common in the insect pest resistance identification of other plant species, as cases can be found in the screening of soybean (334 genotypes) resistant to aphid ( Aphis glycines ) ( Bhusal et al., 2013 ), pepper (50 accessions) resistant to green peach aphid ( Myzus persicae ) ( Frantz et al., 2004 ), cotton (over 400 cultivars) resistant to whitefly ( Bemisia tabaci ) ( Li et al., 2016 ), and maize (38 genotypes) resistant to fall armyworm ( Spodoptera frugiperda ) ( Soujanya et al., 2022 ). In those studies, no more than seven resistant genotypes/accessions/cultivars were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf damage rating (LDR) due to FAW was performed on a 1-9 scale, as described by several researchers [18,[30][31][32][33]. The scale was used to categorize the maize genotypes as resistant (1-4), moderately resistant (>4-6), and susceptible (>6-9) [34]. Scoring for LDR was performed four times for the entire plants in the plot, at 42, 49, 56, and 63 days after sowing.…”
Section: Data Collectionmentioning
confidence: 99%